The cosmos and the wonder of responsibility - Alessandro Cavicchia (Carthaginensia, 2025)
The contribution explores the biblical conception of creation, emphasizing humanity's solidarity with it, as reflected in foundational passages such as Gen 1:26–28 and 2:7.16–17. It refutes the erroneous interpretation of dominion as a license for destruction, highlighting instead that human moral action impacts creation, calling humanity to covenantal fidelity for universal prosperity and salvation. The Fourth Gospel confirms God's loving attitude toward creation through the Word-Wisdom and the Incarnation, which reveal the profound unity between Creator and creature. While acknowledging the tension with the human world that rejects the revelation of the Word, Christ's salvific mission aims to address the world’s sin and achieve universal salvation. Similarly, Pauline thought reveals a redemptive process encompassing all creation, urging believers to live with wisdom (fronéin) inspired by Christ and the Spirit, oriented toward universal good and salvation.